Bibliometric analysis of the published articles in the "Minería y Geología" magazine in the period 2000-2010 - Aguirre Arauz, Arianna; Ortiz Nuñez, Roelvis (Revista General de Información y Documentación, 2013)
Is carried out a bibliometric study to measure the behavior of the scientific production of the investigators of the Higher Institute Mining and Metallurgist of Moa, through the articles published in the magazine Mining and Geology in the period 2000-2010. Is presented to the group of investigators that publish in this magazine, as well as the quantification of the works titles published by them; technical bibliometrics is applied for its study. Of the analysis are obtained results about the scientific productivity of the authors, the annual scientific productivity, the behavior of the scientific productivity for educational departments and the thematic about that more is published. A total of 237 publications are register in the studied period and the year 2000 is the most productive of those studied.